ANALISIS PERAN AKUNTANSI KEBERLANJUTAN DALAM MENDUKUNG KUALITAS PENGUNGKAPAN ESG BERBASIS STANDAR GRI: STUDI KASUS PT INDOFOOD SUKSES MAKMUR TBK - Anggi Mayrizka; Jihan Bintang; Titiek Rachmawati (Merwin Publisher, 2026)
This study examines the role of sustainability accounting in supporting the quality of Environmental, Social, and Governance (ESG) disclosure at PT Indofood Sukses Makmur Tbk, with a focus on evaluating its compliance with the Global Reporting Initiative (GRI) standards. Despite the growing importance of ESG reporting in Indonesia, driven by OJK Regulation No. 51/POJK.03/2017, empirical studies that critically assess the quality and measurability of ESG disclosures in Indonesian manufacturing companies remain limited. This research addresses that gap through a qualitative content analysis approach, systematically coding and evaluating the company’s 2023 Sustainability Report and Annual Report against specific GRI indicators (GRI 302, 305, 306, 401, 403, 413, 205, and 415). The findings reveal that while the company has implemented ESG principles across environmental, social, and governance dimensions, the overall quality of disclosure remains suboptimal. In the environmental dimension, only GRI 302 (Energy) was partially fulfilled with quantitative data, while GRI 305 (Emissions) and GRI 306 (Waste) remained largely descriptive. In the social dimension, indicators related to occupational health and safety (GRI 403) were partially disclosed, whereas community engagement (GRI 413) lacked measurable performance indicators. In the governance dimension, transparency and regulatory compliance were adequately reported, but anti-corruption practices (GRI 205) lacked quantitative disclosure.